Impact Analysis of the SHG-Bank Linkage Model on Empowerment of Women in Dehradun - Sonam; Aggarwal, Sushma; Bhushan, Varun (Arthshastra Indian Journal of Economics & Research, 2019)
The SHG-bank linkage model of microfinance is the dominant model of microfinance in India. In this paper, using a sample survey data of 400 women respondents in Dehradun, we examined the political and economic impact of microfinancial activities on the SHG members. We looked at a broader set of indicators for political participation of women. Using Poisson regression, we found that SHG membership led to economic and political empowerment of members in Dehradun. In particular, the impact was more pronounced in Sahaspur as compared to Chakrata. The intercept term in the Poisson regression was found to be significant for both economic and political empowerment for both the regions. We found that this differential impact was due to various factors such as infrastructure and role of NGOs in handholding support such as training of members and access to markets. Our study suggested that mere dispersal of loans should not be the objective of the authorities under the bank - linkage program ; rather, supporting infrastructure and services are very essential for the end use of credit. The purpose of loans to create micro-entrepreneurs who can run their businesses by using the loan money on a sustainable basis should be fulfilled.